(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As the Non Profit Making Organization, NGOs have become an essential part of social upliftment in the Rajasthan state as NGOs undertakes task-oriented and driven by people with a common concern, NGOs perform a range of service and compassionate functions, brings citizen concern to Governments, advocate and monitor course of action and persuade political participation through the provision for the retrieval process of useful information. In the state of Rajasthan, NGOs makes continuous efforts to mobilize resources for the community development through the various channels and positively contributing to sustainable community development by promoting awareness programmes by continuously involve themselves in social development programmes and welfare activities of the rural and urban communities. These NGOs are very well known for taking part of various welfare programmes running by the Government.It would be appropriate to mention that the State Government and NGOs have created a new era of partnership in working for Child Women Welfare , Education, Poverty, Health Care, AIDS Awareness, Employment, Human Rights, Women Empowerment, SCST Welfare, Old Age Homes for Old Age Persons, Upliftment of specially Slum Children and Women etc. in a foremost role. In this situation some selected NGOs are sincerely playing very vital role for Social Justice, Education, Health, Disaster Management, Agriculture, Social Awareness, Betterment of Backward and underprivileged Communities and Poverty.NGOs have also executing the programmes such as linked to Employment, Female Feticides, Rain Water Harvesting, Animal Welfare, Science and Technology, Sports, Development of Art, Craft and Culture, Heritage Protection of Monuments, Conservation of Historical Places, The issues like Conservation and Protection of Environment, Human Rights, Social Equality, Drinking Water issues, Legal Awareness and Aid, Nutrition, Right to Information, Rural and Urban Development, Forming and Supporting Self Help Groups, Research and Development are main part of the major active NGOs in Rajasthan.Basic cardiac principles of NGOs to provide analysis, expertise as well spreading knowledge and awareness for education, empowerment and uplifting our society. Therefore, this paper enunciates the aiming of NGOs in the social development of Rajasthan. It is a case study of 07 NGOs immersed in numerous social dimensions like healthcare, eradicating hunger, poverty and malnutrition, promoting health care, nutrition, sanitation and safe drinking water in Rajasthan. With their ongoing efforts and attracting campaigns, they are continuously focusing their working towards living standards of the society. This research paper is based on secondary data collected from magazines, newspapers, books, journals, websites and other printed material. This paper also deals with the impactful CSR initiatives taken by the NGO division of various companies for the economic growth of Rajasthan.